Serum uric acid as marker of severity of pre-eclampsia - Toshniwal, Shirish; Lamba, Aakriti R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In pre-eclampsia, there is increased uteroplacental resistance and reduced foetal perfusion due to inadequate invasion of spiral arterioles by trophoblast cells. This causes impaired foetal growth and foetal hypoxia. To assess the usefulness of foetal Doppler in predicting adverse perinatal outcome in preeclampsia. Methods: All the women with preeclampsia from 30 weeks onwards were enrolled in the study. The umblical artery (UA) Systolic-diastolic (S/D) ratio >2 standard deviation (SD) or UA - Pulsatility Index (PI) and UA - Resistive Index (RI) >2 SD were taken as abnormal. The middle cerebral artery (MCA) was visualised and cerebroumblical PI ratio calculated. MCA-RI <2SD was taken as abnormal. Results: There were 107 women in the study. Major adverse outcomes 11. Umbilical artery - S/D ratio >2SD (RR 4.46, 95%, CI 1.40-14.17) and RI >2SD (RR 3.36, 95%, CI 1.03-10.61) and MCA RI <2SD (RR 4.46, 95% CI 1.4-14.17) had a high relative risk to predict adverse major perinatal outcome. 39 babies were admitted in neonatal nursery and no parameters could predict them. Though UA - PI >2SD predicted acute foetal distress in labour (RR 2.33, 95% CI 1.21-4.47), there was no association on multivariate regression analysis. Conclusions: This study showed UA-S/D ratio and UA-RI >2SD are significant predictors of perinatal deaths and immediate neonatal resuscitation in preeclampsia. Acute foetal distress in labour or neonatal nursery admission could not be predicted.